An Exploratory Cohort Study Comparing Prothrombin Complex Concentrate and Fresh Frozen Plasma for the Treatment of Coagulopathy After Complex Cardiac Surgery. (July 2015) - Ortmann, Erik; Besser, Martin W.; Sharples, Linda D.; Gerrard, Caroline; Berman, Marius; Jenkins, David P.; Klein, Andrew A.
Abstract : BACKGROUND: Administration of coagulation factor concentrates to treat bleeding after cardiac surgery with cardiopulmonary bypass might be a strategy for reducing allogeneic blood transfusions, particularly for patients treated with warfarin preoperatively. We performed an exploratory analysis on whether the use of prothrombin complex concentrate (PCC) is safe and effective compared with fresh frozen plasma (FFP) to treat coagulopathy after pulmonary endarterectomy surgery with deep hypothermic circulatory arrest. METHODS: Consecutive adult patients who underwent pulmonary endarterectomy surgery between January 2010 and September 2012 and received PCC or FFP to treat coagulopathy were studied. Blood loss during the first 12 hours of admission to the intensive care unit and patient outcomes were compared with propensity score adjustment. RESULTS: Three hundred fifty-one patients underwent pulmonary endarterectomy surgery, all of whom had warfarin discontinued for up to 5 days before surgery; bleeding complications requiring transfusion of blood products were observed in 108 (31%) patients. Of those, 55 received only FFP and 45 received only PCC, whereas 8 received both. Blood loss was significantly greater in the FFP group compared with the PCC group after 12 hours (median [interquartile range], 650 mL [325–1075] vs 277 mL [175–608], P = 0.008). However, there was no difference in the frequency of patients receiving a red blood cell transfusion (number [percent], 44 [80%] vs 34 [76%], P = 0.594) or in the number of units of red blood cells transfused (median [interquartile range], 2 [1–4] vs 3 [1–5] units, P = 0.181). The final propensity score included preoperative international normalized ratio, postoperative activated partial thromboplastin time, and postoperative platelet count. After inclusion of the propensity score in the regression analyses, there were no differences between patients receiving only PCC and patients receiving only FFP in the need for renal replacement therapy (odds ratio [OR] 2.39, 95% confidence interval [CI] 0.51–11.20, P = 0.27), 30-day-mortality (OR 0.32, 95% CI 0.03–3.36, P = 0.35), intracranial hemorrhage (OR 0.73, 95% CI 0.14–3.89, P = 0.71), hospital length of stay (hazard ratio 0.77, 95% CI 0.50–1.19, P = 0.24), or duration of intensive care stay (hazard ratio 0.91, 95% CI 0.59–1.40, P = 0.66). CONCLUSIONS: This retrospective analysis suggests that PCC may be an alternative to FFP in patients previously treated with warfarin who are coagulopathic after major cardiac surgery. Randomized controlled studies powered to evaluate efficacy and important postoperative outcomes for patients receiving PCC versus FFP for coagulopathic bleeding after cardiopulmonary bypass are warranted. Abstract : Published ahead of print Match 27, 2015